Half-metallic ferromagnets - Kübler, Jürgen; Fecher, Gerhard H.; Felser, Claudia (Springer Netherlands, 2013)
Half-metallic ferromagnetism and the related ferrimagnets are reviewed from a theoretical point of view. Concentrating on Heusler compounds as well as the double perovskites we discuss the electronic structure, the nature of the magnetic moments, and the physics of the energy-gap in one of the spin-channels. The role of spin-orbit coupling is examined and a brief account is given of a tetragonal Heusler compound. Exchange interactions are determined and used for calculations of the Curie temperatures and spin-wave spectra. In view of the large Curie temperatures of the Heusler compounds and the double perovskites we discuss double-exchange and super-exchange models.
CRIS-Team Scopus Importer:2023-03-20